Best Answer

Maybe you mean y2y8y6 = 2*8*6 *y^3 = 96y^3. This is not 1. Otherwise, I do not know what you could mean by Y 2y8y 6.

Q: How is Y 2y8y 6 equivalent to 1?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

y-2y8y-6 1y-2y8y-6 1y-6y-6 5y-6 1y

1. the answer is 1.

If you mean y-6 = -4(x+1) then it is a straight line equation equivalent to y = -4x+2 when completed whereas the slope is -4 and the y intercept is 2

If for x = -1 we find the same value of y in both equations, then x = -1 will be a part of the solution of the system.Let's suppose that x = -1 is the x-coordinate of the solution of the given systemx + y = 4x - y = 6.x + y = 4-1 + y = 4-1 + 1 + y = 4 + 1y = 5x - y = 6-1 - y = 6-1 - 6 + y - y = 6 - 6 + y-7 = ySince we have two different values for y, we say that x = -1 is not a part of the solution for the given system.

here is the formula... y-y1=m(x-x1) solution.. y-(-1)=m(x-(-1)) m= (0,-5) (-1,-1) -1-5/-1-0= -6/-1 or +6/6 y-(-1)=6(x--1) y+1=6(x+1) y+1=6x+6 y=6x+6-1 y=6x+5 form of y=mx+b y=6x+5 form of Ax+By+C=0 6x-y+5=0

Related questions

y-2y8y-6 1y-2y8y-6 1y-6y-6 5y-6 1y

1. the answer is 1.

If you mean y-6 = -4(x+1) then it is a straight line equation equivalent to y = -4x+2 when completed whereas the slope is -4 and the y intercept is 2

6

If for x = -1 we find the same value of y in both equations, then x = -1 will be a part of the solution of the system.Let's suppose that x = -1 is the x-coordinate of the solution of the given systemx + y = 4x - y = 6.x + y = 4-1 + y = 4-1 + 1 + y = 4 + 1y = 5x - y = 6-1 - y = 6-1 - 6 + y - y = 6 - 6 + y-7 = ySince we have two different values for y, we say that x = -1 is not a part of the solution for the given system.

here is the formula... y-y1=m(x-x1) solution.. y-(-1)=m(x-(-1)) m= (0,-5) (-1,-1) -1-5/-1-0= -6/-1 or +6/6 y-(-1)=6(x--1) y+1=6(x+1) y+1=6x+6 y=6x+6-1 y=6x+5 form of y=mx+b y=6x+5 form of Ax+By+C=0 6x-y+5=0

Given: y = -2x + 6 x = 1 y = -2(1) + 6 y = 4 I believe this is what you meant. Possibly you meant: y = -2x + 6 + x = 1 Then you would get y = 1 -x + 6 = 1 x = 5

-1

No because y/y is equivalent to 1 which is a rational number

y=4x-6 and x=1 Just replace the x in the first equation with 1 and solve. y=4(1)-6 y= (-2)

Let the 2 numbers be 'x' and 'y': then, x + y = -2 => x = -2 -y -- (1) Also, x * y = -5 -- (2) Put (1) in (2), we have (-2 -y) * y = -5 -2y -y^2 = -5 y^2 + 2y - 5 = 0 We cannot factorize these numbers easily, so we will have to use the Quadratic Formula to solve this: y=( -b ± √( b^2 - 4ac )) / ( 2 * a ) =(-2 ± √( 2^2 -4*1*-5 )) / (2 * 1 ) =(-2 ± √(24)) / 2= -1 ± 2 * √(6) / 2=-1 ± √(6) We can substitute these values into x=-y-2: x=-(-1 + √(6)) - 2 = 1 - √(6) - 2= -1 - √(6) x=-(-1 - √(6)) - 2 = 1 + √(6) - 2= -1 + √(6) Therefore: x=-1-√(6) y=-1+√(6) OR x=-1+√(6) y=-1-√(6)

For example, if you have (0, 6) or (3, 1). Which of them is a solution to y - 2x = 6? Check (0, 6): y - 2x = 6, substitute 0 for x, and 6 for y into the equation 6 - 2(0) =? 6 6 - 0 =? 6 6 = 6 True, then (0, 6) is a solution. Check (3, 1): y - 2x = 6, substitute 3 for x, and 1 for y into the equation 1 - 2(3) =? 6 1 - 6 =? 6 -5 = 6 False, then (3, 1) is not a solution.